Three-dimensional surface displacement tracking for in-situ experiments: An alternative to digital image correlation (DIC). (February 2023) - El-Awady, Khalid A.; Lavenstein, Steven; El-Awady, Jaafar A.
Abstract: We develop an approach for tracking the three-dimensional (3D) surface displacements of a material undergoing in situ mechanical testing inside a scanning electron microscope. Specifically, we estimate the out-of-plane intrusions/extrusions and in-plane motion of surface points from multiple views of the sample at the end of the experiment. Then, using reverse optical flow, propagate these displacements backwards in time using interim single view images. These measurements can be extended to map the 3D surface strain tensors. This approach offers an alternative to the commonly used digital image correlation (DIC) technique, which relies on tracking a speckle pattern applied to the material surface. DIC based on single views only produces in-plane two-dimensional (2D) measurements, whereas our approach enables reconstruction of the 3D surface morphology and is completely non-invasive (requires no pattern being applied to the material surface).